Is It Possible for Light-Based Hair Removal Home Devices to Induce Ocular Damage? Systematic Review - Al muqarrab FJ; Alsuwaidan S; Al muqarrab Z; Alajlan A (Dove Medical Press, 2023)
Fatimah J Al muqarrab,1 Sami Alsuwaidan,1 Zahraa Al muqarrab,2 Abdulmajeed Alajlan1 1Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Department of Dermatology, College of Medicine, King Faisal University, Hofuf, Saudi ArabiaCorrespondence: Fatimah J Al muqarrab, Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia, Tel +966-545772444, Email fatimah.muq12@gmail.comAbstract: Light-based hair removal home devices emit intense pulse light (IPL) or Diode laser. While the Food and Drug Administration controls them in the US, Europe continues to classify them as cosmetic products. Emerging concerns are: what if an unprotected eye is inadvertently exposed to light emission? Or if the consumer tries to overcome the protective safety features? We performed this systematic review by searching the Medline, CENTRAL, and Google Scholar databases to investigate the ocular damage reported after exposure to IPL for hair removal. We could not identify any case reported following exposure to home devices; however, a total of 20 patients were identified with iris atrophy, anterior chamber inflammation, and/or retinal pigment epithelium damage following exposure to office IPL or Diode lights. 40% were not using any protective eyewear during the light procedure. The reported fluences were in the range of 20– 24 J/cm2. Although the ocular damage was identified following office devices, the reported fluences were within the home device’s limits. For that, manufacturers should provide clear instructions on the package regarding the ocular hazards, the importance of using protective goggles, and a firm warning not to overcome the contact sensors. Home device-induced ocular damage is still a concern, perhaps under-reported.Keywords: light-based home devices, IPL, intense pulse light, laser safety, hair removal, ocular damage